An Analysis of Business Administration Student’s Needs for English Public Speaking Ability - Mulyadin, Asrul (STIA Adabiah, 2025)
The aims of this study to analyse the needs of Business Administration Students of STIA Adabiah related to Public Speaking to prepare graduates who are competent in speaking in public using English as a provision to face the global era. There is a desire and hope that graduates of the Business Administration Students have global competitiveness in addition to science related to administration. To maximize the potential of the next candidate for Business Administration graduates, a material design is needed to improve Public Speaking skills by first analysing the Public Speaking skill needs that are most needed by the study program. This study analyses the needs of expected materials from a semi-structured interview with the Head of the Business Administration Study Program. The results of the research show that the Business Administration students want to focus on learning objectives on improving communication skills based on the future job needs of graduates seen through tracer studies to make graduates more job-ready.